Muscarinic Acetylcholine Type 1 Receptor Activity Constrains Neurite Outgrowth by Inhibiting Microtubule Polymerization and Mitochondrial Trafficking in Adult Sensory Neurons - Sabbir, Mohammad G.; Calcutt, Nigel A.; Fernyhough, Paul (Frontiers in Neuroscience, 2018)
The muscarinic acetylcholine type 1 receptor (M1R) is a metabotropic G protein-coupled receptor. Knockout of M1R or exposure to selective or specific receptor antagonists elevates neurite outgrowth in adult sensory neurons and is therapeutic in diverse models of peripheral neuropathy. We tested the hypothesis that endogenous M1R activation constrained neurite outgrowth via a negative impact on the cytoskeleton and subsequent mitochondrial trafficking. We overexpressed M1R in primary cultures of adult rat sensory neurons and cell lines and studied the physiological and molecular consequences related to regulation of cytoskeletal/mitochondrial dynamics and neurite outgrowth. In adult primary neurons, overexpression of M1R caused disruption of the tubulin, but not actin, cytoskeleton and significantly reduced neurite outgrowth. Over-expression of a M1R-DREADD mutant comparatively increased neurite outgrowth suggesting that acetylcholine released from cultured neurons interacts with M1R to suppress neurite outgrowth. M1R-dependent constraint on neurite outgrowth was removed by selective (pirenzepine) or specific (muscarinic toxin 7) M1R antagonists. M1R-dependent disruption of the cytoskeleton also diminished mitochondrial abundance and trafficking in distal neurites, a disorder that was also rescued by pirenzepine or muscarinic toxin 7. M1R activation modulated cytoskeletal dynamics through activation of the G protein (Gα13) that inhibited tubulin polymerization and thus reduced neurite outgrowth. Our study provides a novel mechanism of M1R control of Gα13 protein-dependent modulation of the tubulin cytoskeleton, mitochondrial trafficking and neurite outgrowth in axons of adult sensory neurons. This novel pathway could be harnessed to treat dying-back neuropathies since anti-muscarinic drugs are currently utilized for other clinical conditions.